2020
DOI: 10.1007/s40194-020-00984-2
|View full text |Cite
|
Sign up to set email alerts
|

Local mechanical properties of explosively welded AA2519-AA1050-Ti6Al4V layered material

Abstract: The study presents the results of tests of local static and cyclic properties of an explosively welded AA2519-AA1050-Ti6Al4V layered material. In order to perform the analysis, tests were carried out with the use of microspecimens collected from 10 layers of AA2519-AA1050-Ti6Al4V material. Additionally, the determined static properties were compared with the results of an analysis based on microhardness measurement. Based on the test results, slight differences in static properties were found for particular la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The micro-specimen tests were performed using the MFS (Micro-Fatigue System) dedicated to static and fatigue tests of micro-objects [ 25 , 26 ]. The load on the specimens in the MFS system is applied using a nano- or a micro-drive.…”
Section: Methodsmentioning
confidence: 99%
“…The micro-specimen tests were performed using the MFS (Micro-Fatigue System) dedicated to static and fatigue tests of micro-objects [ 25 , 26 ]. The load on the specimens in the MFS system is applied using a nano- or a micro-drive.…”
Section: Methodsmentioning
confidence: 99%
“…Micro-specimens were tested using the Micro Fatigue System (MFS) dedicated to static and fatigue testing of micro-objects [34,35]. Specimens in the MFS system are loaded using a nano-or microdrive.…”
Section: Methodsmentioning
confidence: 99%
“…The last factor is especially important for the EW of titanium, because titanium particles burn in the air present in the welding gap, which has a negative effect on the mechanical properties of the weld [29]. Studies [30,31] showed examples of EW of Ti6Al4V to AA2519, with and without an interlayer of AA1050. The results showed that EW is an effective method of producing Ti6Al4V-AA2519 bimetals without defects.…”
Section: Introductionmentioning
confidence: 99%